ANALISIS TINDAK TUTUR DIREKTIF DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS VIII SMP SILA DHARMA - Karolus Samin; Ida Ayu Made Wedasuwari; Dewa Gede Bambang Erawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
Research is to describe the form of directive speech acts of teachers and students in class VIII SMP Sila Dharma in the process of learning Indonesian. This research is a type of qualitative research, literature study, field study, and a combination of both. The data source is from Directive Speech Acts in Class VIII Indonesian Language Learning at SMP Sila Dharma. Data collection techniques using the method of observation and methods of literature. The results of the analysis show that there is an Analysis of Speech Acts in Indonesian Language Learning at Class VIII Sila Dharma Middle School. the researcher found 28 forms and functions of directive speech acts. Of the 28 forms of directive speech acts include: 5 directive speech acts asking, 3 directive speech acts ordering, 5 directive speech acts begging, 5 directive speech acts suggesting, 5 directive speech acts inviting, 1 directive speech act giving a signal, 3 speech acts directive challenge and 1 speech act directive charge.